Invoking the Specter of Racism: Category Membership as Speaker Topic and Resource - McKenzie, Kevin (Qualitative Sociology Review, 2016)
This paper explores how category membership features in talk where speakers address the issue of racial discrimination. In particular, it examines how category membership gets invoked to furnish speaker entitlement in the course of destabilizing and reworking the category-bound inferences that inform membership attribution. I begin with the analysis of two relatively short extracts of talk in which speakers invoke ethnic and racial group identity as a preliminary to an examination of the paradoxical uses for which category membership is made relevant, moving on to consider an extended episode of The 700 Club. In contrast to analytic approaches which seek to reveal the denial of racism in speaker claims that mitigate the pernicious implications of category attribution, I consider how category attribution serves as a speaker resource in efforts to identify and critique racism. This participant work is then considered in relation to ethnomethodology’s efforts to re-specify the foundational postulates that inform the investigation of social order production and the place that the examination of participant meaning-making has in the pursuit of that endeavor.